An in vitro growth inhibition test for measuring the potency of Leptospira spp. Sejroe group vaccine in buffaloes - de Nardi Junior, Geraldo; Genovez, Margareth Elide; Ribeiro, Márcio Garcia [UNESP]; Castro, Vanessa; Jorge, Andre Mendes [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2010)
Leptospira spp. serovars Hardjo and Wollfi from Sejroe serogroup have been detected in livestock in Brazil, where the main control procedures rely on vaccination. The potency of two commercial vaccines available in this country was monitored by microagglutination test-MAT and in vitro growth inhibition test-GIT in serum samples from 33 female buffaloes divided into: G1-unvaccinated control; G2-vaccinated with Leptobac-6 (R) containing serovars Hardjo and Wolffi and G3-vaccinated with Triangle-9 (R) containing serovar Hardjo. G2 and G3 animals were vaccinated on day zero, and received a booster and two revaccinations on days 30, 210 and 390 and G1 animals received phosphate buffered saline. Serum samples were collected at 15-day intervals between days 0 and 60; and at 30-day intervals between days 60 and 540 and were tested by MAT and GIT with serovars Hardjo and Wolffi. G1 remained negative throughout the experiment. Both vaccines were able to induce agglutinating and growth inhibition antibodies. Six months after the last revaccination, all animals tested negative by MAT, but still were positive by GIT until the end of experimental period. GIT could be a good tool to evaluate the potency and to monitor antibodies responses of vaccines of Sejroe group serovars. (C) 2010 The International Association for Biologicals. Published by Elsevier Ltd. All rights reserved.
Keywords: Buffalo; Leptospira spp. serovar Hardjo; Leptospira spp. serovar Wolffi; Leptospirosis vaccine; Leptospira growth inhibition test